Odpowiedzi

2010-02-04T18:57:50+01:00
1)
a)1/3x-2=x+2
x-1/3x=-4
2/3x=-4
x=-6
b)1-6/7x=4/7x
6/7x=1-4/7
6/7x=3/7
x=1/2
c)6(1/4x-2)=18
3/2x-12=18
3/2x=30
x=20
d)x/6-1/6=1
x-1=6
x=6+1
x=7
e)-2(2x-1)=x/3
-4x+2=x/3
-12x+6=x
6=13x
x=6/13
f)2/5(3-x)=-2
6/5-2/5x=-2
2/5x=16/5
x=8
g)3/4(2-3x)=-6
6/4-9/4x=-6
9/4x=6/4+6
9/4x=30/4
x=3 i 1/3
h)1/5(x-3)=9-x
1/5x-3/5=9-x
1/5x+x=9+3/5
6/5x=48/5
x=8
i)(0,6+x)/2=x+1
0,6+x=2x+2
2x-x=0,6-2
x=-1,4
2)a)((x+12)6)/2=42
(6x+72)/2=42
6x+72=84
6x=84-72
6x=12
x=2
b)((4x-2)4)/2=44
(16x-8)/2=44
16x-8=88
16x=80
x=5
c)2x+2(2x-8)=28
2x+4x-16=28
6x=28+16
6x=44
x=7 i 1/3